The respiratory compensation point: Mechanisms and relation to the maximal metabolic steady state - Keir, D. A.; Pogliaghi, S.; Inglis, E. C.; Murias, J. M.; Iannetta, D. (Sports Medicine, 2024)
At a point during the latter third of an incremental exercise protocol, ventilation begins to exceed the rate of clearance of carbon dioxide (CO2) at the lungs (CO2). The onset of this hyperventilation, which is confirmed by a fall from a period of stability in end-tidal and arterial CO2 tensions (PCO2), is referred to as the respiratory compensation point (RCP). The mechanisms that contribute to the RCP remain debated as does its surrogacy for the maximal metabolic steady state of constant-power exercise (i.e., the highest work rate associated with maintenance of physiological steady state). The objective of this current opinion is to summarize the original research contributions that support and refute the hypotheses that: (i) the RCP represents a rapid, peripheral chemoreceptor-mediated reflex response engaged when the metabolic rate at which the buffering systems can no longer constrain the rise in hydrogen ions ([H+]) associated with rising lactate concentration and metabolic CO2 production is surpassed; and (ii) the metabolic rate at which this occurs is equivalent to the maximal metabolic steady state of constant power exercise. In doing so, we will shed light on potential mechanisms contributing to the RCP, attempt to reconcile disparate findings, make a case for its adoption for exercise intensity stratification and propose strategies for the use of RCP in aerobic exercise prescription.